Deep brain stimulation in childhood: an effective treatment for early onset idiopathic generalised dystonia. - Parr, JR; Green, A; Joint, C; Andrew, M; Gregory, R; Scott, R; McShane, M; Aziz, T (2007)
BACKGROUND: Early onset idiopathic generalised dystonia is a progressive and profoundly disabling condition. Medical treatment may ameliorate symptoms. However, many children have profound, intractable disability including the loss of ambulation and speech, and difficulties with feeding. Following the failure of medical management, deep brain stimulation (DBS) of the globus pallidus internus (GPi) has emerged as an alternative treatment for the disorder. METHODS: We describe four children who presented with dystonia. RESULTS: Following the failure of a range of medical therapies, DBS systems were implanted in the GPi in an attempt to ameliorate the children's disabilities. All children found dystonic movements to be less disabling following surgery. Compared with preoperative Burke, Fahn and Marsden Dystonia Rating Scale scores, postoperative scores at 6 months were improved. CONCLUSIONS: DBS is effective in improving symptoms and function in children with idiopathic dystonia refractory to medical treatment. Whilst surgery is complex and can be associated with intraoperative and postoperative complications, this intervention should be considered following the failure of medical therapy.